Genome-wide characterization of ovate family protein gene family associated with number of seeds per silique in Brassica napus - Liu, Jie; Wu, Yupo; Cui, Xiaobo; Zhang, Xiong; Xie, Meili; Liu, Lijiang; Liu, Yueying; Huang, Junyan; Cheng, Xiaohui; Liu, Shengyi (Frontiers in Plant Science, 2022)
Ovate family proteins (OFPs) were firstly identified in tomato as proteins controlling the pear shape of the fruit. Subsequent studies have successively proved that OFPs are a class of negative regulators of plant development, and are involved in the regulation of complex traits in different plants. However, there has been no report about the functions of OFPs in rapeseed growth to date. Here, we identified the OFPs in rapeseed at the genomic level. As a result, a total of 67 members were obtained. We then analyzed the evolution from Arabidopsis thaliana to Brassica napus, illustrated their phylogenetic and syntenic relationships, and compared the gene structure and conserved domains between different copies. We also analyzed their expression patterns in rapeseed, and found significant differences in the expression of different members and in different tissues. Additionally, we performed a GWAS for the number of seeds per silique (NSPS) in a rapeseed population consisting of 204 natural accessions, and identified a new gene BnOFP13_2 significantly associated with NSPS, which was identified as a novel function of OFPs. Haplotype analysis revealed that the accessions with haplotype 3 had a higher NSPS than other accessions, suggesting that BnOFP13_2 is associated with NSPS. Transcript profiling during the five stages of silique development demonstrated that BnOFP13_2 negatively regulates NSPS. These findings provide evidence for functional diversity of OFP gene family and important implications for oilseed rape breeding.